Report of double wall in hepatopancreatic tubules in marine shrimp, conceptual error and tissue impossibility - Varela, Alexander (2021)
In this note, some bacterial pathologies with the capacity to injure the hepatopancreas of farmed marine shrimp are cited, as well as details of some of the monitoring techniques used for their study, emphasizing the fresh analysis. This technique is widely used in shrimp farms due to its low cost, minimum response time, short training time and practicality. The issue of the so-called «double wall» reported with some frequency by some analysts is addressed, presenting arguments to understand the possible origin of this artifact, and the impossibility of the formation of multiple walls in the tubules is supported with information. For this, the normal structure of the tubular epithelium of these animals is described, both in normal stages, as well as under pathological conditions.